Dinamika Kepatuhan Pajak: Studi Kasus Pemahaman Wajib Pajak dan Implementasi Self-Assessmenet di KPP Pratama Jember - Sholehah, Lutfiatus; Maulana Muhamad Maliki Al Jawani; Diana, Itri (Jurnal Ilmiah Raflesia Akuntansi, 2025)
This study examines the dynamics of tax compliance with a focus on the impact of taxpayer understanding and the implementation of the self-assessment system at the Jember Tax Office (KPP). This study uses a qualitative approach through case studies with direct observation and structured interviews with individual taxpayers from various occupational backgrounds. The results of the study show that although most taxpayers have a general understanding of income tax (PPh 21), many still do not understand important matters such as the limits of non-taxable income (PTKP), reporting deadlines, and reporting procedures via DJP Online, particularly the use of Form 1770 S, which can pose challenges in fulfilling tax obligations accurately and on time. The self-assessment system allows taxpayers to calculate, pay, and record their own taxes. However, there are still barriers in tax literacy and adaptation to digitalized services, which impact tax compliance. Assistance programs such as RENJANI (Domestic Tax Volunteers) have proven to improve compliance through education and direct assistance. This study emphasizes the importance of increasing the intensity of tax socialization and education, particularly regarding reporting procedures and the use of online systems, to make the self-assessment system more effective. Overall, this research concludes that taxpayers' understanding and the effectiveness of self-assessment implementation have a significant influence on tax compliance behavior. Therefore, it is recommended to optimize consultation services, enhance education, and strengthen the role of tax officials in providing information and guidance to support optimal tax compliance and a more transparent tax system within the Jember Tax Office